1988
DOI: 10.1126/science.2461587
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Developmentally Mutated Human Globin Genes by Cell Fusion

Abstract: Human fetal globin genes are not expressed in hybrid cells produced by the fusion of normal human lymphocytes with mouse erythroleukemia cells. In contrast, when lymphocytes from persons with globin gene developmental mutations (hereditary persistence of fetal hemoglobin) are used for these fusions, fetal globin is expressed in the hybrid cells. Thus, mutations of developmental origin can be reconstituted in vitro by fusing mutant lymphoid cells with differentiated cell lines of the proper lineage. This system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0
1

Year Published

1990
1990
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 10 publications
1
14
0
1
Order By: Relevance
“…Mutated (HPFH) human fetal globin genes are activated in stable somatic cell hybrids (29). In this report, we show that in transient heterokaryons formed by fusion of MEL cells with cells from several different HPFH cell types, the mutated (HPFH) fetal genes are rapidly activated.…”
mentioning
confidence: 74%
“…Mutated (HPFH) human fetal globin genes are activated in stable somatic cell hybrids (29). In this report, we show that in transient heterokaryons formed by fusion of MEL cells with cells from several different HPFH cell types, the mutated (HPFH) fetal genes are rapidly activated.…”
mentioning
confidence: 74%
“…Lymphoid cells from a Hispanic thalassemia individual, immortalized with Epstein-Barr virus, were fused with MEL cells, selected, and propagated as described (Takegawa et al 1986;Papayannopoulou et al 1988). Briefly, MEL cells were mixed with human lymphoid cells at 1 : 10 ratio, and 50% polyethylene glycol (PEG, vol/vol) was added in RPMI-1640 media at 37~ Cells were then washed, resuspended in RPMI plus 10% fetal calf serum, and cultured for 48 hr prior to selection for hybrid phenotype.…”
Section: Somatic Cell Hybridsmentioning
confidence: 99%
“…Previous work has shown that these hybrids faithfully reproduce normal and mutant globin gene expression and thereby constitute a model system to study globin gene regulation (Papayannopoulou et al 1988).…”
mentioning
confidence: 99%
“…Hybrid aliquots which had been cryopreserved before the onset of the ␥-to-␤ switch were used in this study. Because addition of sodium butyrate to the culture medium induces terminal differentiation of MEL cells (15,16,21), we used ␣-ABA instead of sodium butyrate; ␣-ABA is a compound which does not, in our experience, trigger terminal differentiation. Cells were grown in the presence of 20% FCS or 20% charcoal-absorbed FCS.…”
Section: Resultsmentioning
confidence: 99%
“…(29,34). When lymphoid cells from persons with hereditary persistence of fetal hemoglobin due either to ␥ gene promoter mutations or to ␦-and ␤ gene deletions are fused with MEL cells, human fetal hemoglobin is produced in the hybrids (21). When erythroid cells from fetuses are fused with MEL cells, the HFE ϫ MEL hybrids produce predominantly human fetal hemoglobin; however, after several weeks in culture, they switch to adult human globin production (20).…”
Section: Discussionmentioning
confidence: 99%